Legal Protection Against Cryptocurrency Investors: Overview of Indonesian Consumer Protection Law - Safina Callistamalva Arindrajaya (Journal of Human Rights, Culture and Legal System, 2022)
Information and communication technology advancements has spawned numerous innovations, including cryptocurrency. Cryptocurrency is a currency that only exists in Indonesia as a digital asset. The volatile and uncontrollable value of cryptocurrencies causes investors to suffer losses. This study aims to determine the legal protection of cryptocurrency investors in Indonesia under Consumer Protection Law. This study employs a descriptive qualitative methodology with a normative approach through legislation. According to the findings of this study, The Consumer Protection Act provides legal protection for cryptocurrency investors by regulating the rights and responsibilities of consumers and business actors.